Blocking the loopholes: Nigeria’s post-war import control (2025)
The end of the Second World War in 1945 ushered in an important epoch in Nigeria’s economic history and this has attracted the interrogation of various historical developments of her post war experience by scholars. This became imperative because the end of the war opened a new chapter in the history of the country. The period marked the beginning of socio-economic and political transformation of colonial Nigeria. To this end, scholars from various disciplines such as economics, sociology, political science and history have paid adequate attention to the country’s post-war events. These include, the decolonisation of the country’s economy through the prism of economics as a discipline, political decolonization, agitations against discriminatory practices against Nigeria’s investors and transfer of power from the British to Nigeria’s political elite. Similarly, scholars have looked at the contributory roles of Nigerians both military and civilians to the success of British prosecution of the Second World War. However, most of these works did not directly examine how the country regulated her imports through the expansion of industries after the Second World War in 1945 up to 1954 when the colonial government granted the three regions greater autonomy to take certain economic decisions with the limited inputs of the colonial regime. This neglect limits our understanding of Nigeria’s post-war economic history. The paper argues that import control through the expansion of industries was deployed as one of the strategies of the decolonisation process which began in the country after 1945.